A Novel Diagnostic Model for Primary Adrenal Lymphoma - Yu, Kai; Xue, Qingping; Zhou, Fangli; Tian, Haoming; Xiang, Qiao; Chen, Tao; Ren, Yan (Frontiers in Endocrinology, 2021)
Objective: Primary adrenal lymphoma (PAL) is easily misdiagnosed with other adrenal masses, like adrenocortical carcinoma and pheochromocytoma, but can hardly benefit from surgery. The diagnostic method for PAL hitherto limits to adrenal biopsy. In our study, we aimed to develop a quick and efficient diagnostic method for PAL. Methods and Results: At the same institution, 505 patients (between 2009 and 2019) and 171 patients (between 2019 and 2020) were separately included in the primary and the validation study. Uni- and multi-variate analysis were conducted to evaluate clinical manifestations, laboratory findings, and radiological characteristics. Four determinants, aAge (Odds ratio (OR), 1.07, 95% confidence interval (CI), 1.02-1.14), bilateral masses (OR, 7.37, 95% CI, 1.44-39.29), high-density lipoprotein cholesterol (OR, 0.12 95% CI, 0.01-0.68), and lactate dehydrogenase (OR, 1.01, 95% CI, 1.01-1.02) were selected as independent key factors and were further incorporated into a nomogram regression model to screen PAL. Accordingly, the nomogram was developed for clinic practice. In the primary study, tThe he nomogram showed good discriminations with area under the receiver operating characteristic (ROC) curve (AUC) of 0.95.4% (95% CI, 90.60%–100.00%) in the primary study. And further validation study verified in the validation studythe efficacy of the nomogram with an AUC of 0.99.0%4 (95% CI, 968.906%–100.00%) and 100.0%, and sensitivity/ specificity/ positive predictive value (PPV)/ negative predictive value (NPV) of 66.67%/ 99.40%/ 66.67%/ 99.40%, 66.67%/ 100%/ 100%/ 92.86%, 50%/ 99.20%/ 50%/ 99.20%, 100%/100%/100%/100%, in all patients, in patients with bilateral adrenal mass, in patients with non-functional adrenal mass, and in patients with positive result of catecholamines, respectively. The validation study also revealed a diagnostic specificity of 99.35% and 100% for patients with unilateral adrenal mass and functional PCC, separately. Conclusions: The presented nomogram was the first user-friendly diagnostic model for PAL that simplified the complex diagnostic process into personalized numeric estimate. We deem that patients who score below 50 are less likely PAL. And we suggest that clinician should arrange adrenal biopsy and surgery for patients with non-functional tumor and overt catecholamine-secretion tumor, separately, who gets a 50-point or higher score, to confirm the diagnosis as soon as possible.